2018
DOI: 10.1080/00016489.2018.1425901
|View full text |Cite
|
Sign up to set email alerts
|

Hearing results after type III tympanoplasty: incus transposition versus PORP. A systematic review

Abstract: An improvement in hearing results was observed within both groups after type III tympanoplasty. There is no difference in decibels gained between both ossiculoplasty materials, but a better closure rate (%) was observed in the PORP group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…However, a heterogeneous population was intentionally included to facilitate a broad investigation of audiometric outcomes from ossiculoplasty procedures as a whole. Despite including a small and heterogeneous study population, our post‐operative ABG outcomes are similar to other published studies reporting hearing outcomes following ossiculoplasty, 15,16,24,34‐36 thus it is reasonable to speculate that other ossiculoplasty patients also have a persistent post‐operative high‐frequency ABG. Similarly, we believe a larger patient cohort may delineate some of the small but statistically significant differences between low‐ and high‐frequency conductive hearing outcomes demonstrated herein; this is an important direction for future research.…”
Section: Discussionsupporting
confidence: 84%
“…However, a heterogeneous population was intentionally included to facilitate a broad investigation of audiometric outcomes from ossiculoplasty procedures as a whole. Despite including a small and heterogeneous study population, our post‐operative ABG outcomes are similar to other published studies reporting hearing outcomes following ossiculoplasty, 15,16,24,34‐36 thus it is reasonable to speculate that other ossiculoplasty patients also have a persistent post‐operative high‐frequency ABG. Similarly, we believe a larger patient cohort may delineate some of the small but statistically significant differences between low‐ and high‐frequency conductive hearing outcomes demonstrated herein; this is an important direction for future research.…”
Section: Discussionsupporting
confidence: 84%
“…[11][12][13][14][15][16] Also in previous study conducted by Iñiguez-Cuadra et al among 56 canal wall down patients 33 and among 37 canal wall up patients 24 had successful ABG closure of 0-20 dB. [17][18][19] In current study, totally 10 cases underwent canal wall down 6 in incus group and 4 in titanium group, one case lost follow up in titanium group. In four cases malleus was totally absent, here in 1 case, the total ossicular replacement prosthesis was used placing it between the temporalis fascia graft and mobile foot plate with cartilage cap in four cases malleus was completely present, where total ossicular replacement prosthesis was placed between malleus and foot plate of stapes in titanium group.In incus group 8 cases had malleus.…”
Section: Discussionmentioning
confidence: 65%
“…The study conducted by Bartel 17 Orfao et al showed a postoperative decrease of 11.0 dB in air-bone gap and 12.4 dB in pure-tone average was observed in titanium ossiculoplasty compared with a reduction of 4.0 dB in air-bone gap and 5.1 dB in puretone average when autologous reconstruction was used. 18 In current study, the mean pre op pure tone average in autologous incus was 52.30 dB and in titanium ossicular replacement prosthesis was 56.11dB.…”
Section: Hearing Gain Characteristicsmentioning
confidence: 96%
“…As well, allografting [13] , in spite of being made to be bio-compatible, is still expensive and till now, there is no solid literature agreement regarding the effectiveness of each one of allografts. Regarding the use of IT technique, Zhang et al in 2011 [1] , firstly, reported that titanium prostheses added no more benefit compared to non-titanium ones and Bartel et al [4] in 2018, secondly, concluded that IT gave comparable efficacy as PORP. We, also, here propose CBA for ossicular reconstruction in cases of moderate hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted by Baylancicek et al 2014 [3] , BC was found to be a reliable, easily available technique with results of hearing gain comparable to partial ossicular replacement prosthesis (PORP) with no significant statistical difference between both procedures. As well, Bartel et al [4] conducted a metaanalysis in 2018 and concluded that incus transposition (IT) gave comparable results to PORP especially regarding decibels gain. In the presence of difficulties in IT, cortical bone autograft (CBA) might present a good substitute.…”
Section: Introductionmentioning
confidence: 99%